Coping strategies in children of parents deceased from cancer and children of parents healed from cancer - Alamdarloo, Ghorban Hemati; Moradi, Shahram; Gholami, Marziyeh; Nazari, Zahra; Amiri, Parvin (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
This study aimed to compare coping strategies in children of parents deceased from cancer and children of parents healed from cancer in the city of Shiraz, Iran. One-hundred and fifteen people [58 children of parents healed from cancer and 57 children of parents deceased from cancer] were recruited in this study via a convenience sampling method. Coping Inventory for Stressful Situations was used to measure different types of coping strategies [task-oriented coping strategy, emotion-oriented coping strategy, and avoidance coping strategy]. The results showed that the children of parents healed from cancer used task-oriented coping strategy significantly more than children of parents deceased from cancer. Moreover, the results showed that the use of emotion-oriented coping strategy in children of parents deceased from cancer was significantly more than children of parents healed from cancer. No significant difference was observed between the two groups in the use of avoidance coping. This study highlights the importance of coping strategies in families with a cancer parent which demands the importance of teaching appropriate coping strategies in order to reduce the adverse consequence of cancer in the family.